Clinico-microbiological and Risk Factor Analysis of Strongyloides stercoralis Infections in South India - Abirami lakshmy Jayachandran; Vandhitha Muralidharan; Balan Kandasamy (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Strongyloides stercoralis is a soil-transmitted nematode infection. It is implicated in causing hyper infection syndrome in immunosuppressed patients. This infection can also present without symptoms. The study aims to analyze the demographic data and risk factors associated with acquiring this infection and detectStrongyloides stercoralis in the stool sample by microscopy and modified agar plate culture. Combining microscopy and culture can facilitate detecting the infection in cases of low worm burden. Evaluation of socio-demographic information and risk factors will help in implementing control measures. A total of 986 stool samples were received. All the samples were examined by saline and Iodine mount examination. All the stool samples were cultured by the modified agar plate method. The risk factors, patient demographic details and clinical features were analyzed for significant association using the Chi-square test and a p-value < 0.05 was considered significant) by quick calls graph pad software. The overall prevalence of Strongyloides stercoralis infection was 22(1.23%), and all these cases were diagnosed on stool examination by the demonstration of rhabditiform larva ofStrongyloides stercoralis and adult females by modified agar plate culture. The positivity for Strongyloides larva was high among males, patients from rural areas and individuals working in agricultural settings. There was a significant association between walking barefoot and the demonstration of the larva. Patients presenting from endemic regions, even with vague, nonspecific gastrointestinal symptoms, especially with risk factors like Diabetes mellitus, should be screened for this infection and treated. Awareness, proper hygiene practices, and appropriate treatment are necessary to prevent this soil-transmitted helminthic infection.